Functional Swallowing Outcomes after Transoral Robotic Supraglottic Laryngectomy. (2nd September 2014) - Bayrak, Sinehan; Davis, Amanda; Vural, Emre A.
Abstract : Objectives: (1) Defining functional swallowing outcomes as well as determining an expected length of time for patients to safely return to a normal oral diet in transoral robotic surgery (TORS) for resection of supraglottic laryngeal cancer. Methods: Retrospective chart review of patients who underwent TORS for resection of laryngeal cancer from 2011‐2013. ASHA's National Outcomes Measurement System, oral diet levels, and dependency on tube feedings were used as outcome measures. Results: Eleven patients were included in this study. Five out of 11 patients completed the treatment program and follow‐up care, 100% returned to full oral diets in an average of 18.6 weeks, and all subsequently had their g‐tube removed. Sixty percent of these patients continued to require compensatory swallowing techniques (ie, supraglottic swallowing maneuver) and/or modified diets (ie, thickened liquids) in order to safely consume oral diet without aspiration. Two patients died; 1 patient was lost to follow‐up; 3 patients were still NPO at last contact. Conclusions: Patients who have undergone supraglottic laryngectomy will likely experience significant dysphagia, but good functional swallowing outcomes should be expected in the intermediate term.